Alternatives to Peer Review: Novel Approaches for Research Evaluation - Birukou, Aliaksandr; Wakeling, Joseph R.; Bartolini, Claudio; Casati, Fabio; Marchese, Maurizio; Mirylenka, Katsiaryna; Osman, Nardine; Ragone, Azzurra; Sierra, Carles; Wassef, Aalam (Frontiers in Computational Neuroscience, 2011)
In this paper we review several novel approaches for research evaluation. We start with a brief overview of the peer review, its controversies, and metrics for assessing efficiency and overall quality of the peer review. We then discuss five approaches, including reputation-based ones, that come out of the research carried out by the LiquidPub project and research groups collaborated with LiquidPub. Those approaches are alternative or complementary to traditional peer review. We discuss pros and cons of the proposed approaches and conclude with a vision for the future of the research evaluation, arguing that no single system can suit all stakeholders in various communities.